Kentucky bourbon : the early years of whiskeymaking - Crowgey, Henry G. (University Press of Kentucky, 2008)
Author "claims that distilled spirits and pioneer settlement went hand in hand, [and] traces the drink's history from its beginnings as a cottage industry to steam-based commercial operations in the period just before the Civil War."--Cover